The Influence of Digital Marketing, Product Quality, and Service on Consumer Purchase Interst at Café Scooterafee Bangil - Febrianti, Nila Osama; Yulianto, Mochamad Rizal; Sumartik, Sumartik (Universitas Negeri Padang, 2024)
Every business actor in each business category is required to have sensitivity to every change that occurs. Digital marketing plays a very important role in business activities, considering its orientation towards providing value to consumers. Café Scooterafee is one of the cafes widely discussed by the millennial generation today. Café Scooterafee can influence consumer purchase intention through the quality of its products and services. The purpose of this study is to determine the variables that have the most significant impact on increasing consumer purchase intention towards Café Scooterafee. The method applied in this research is a quantitative approach. A total of 100 respondents were selected using the Lemeshow formula. The results of this research indicate that three variables digital marketing influence, product quality, and service quality significantly affect consumer purchase intention towards Café Scooterafee.Keywords: Digital Marketing, Product Quality, Service Quality, Consumen Buying Interest